2019
DOI: 10.2147/jpr.s223190
|View full text |Cite
|
Sign up to set email alerts
|

<p>Emotional Effects on Factors Associated with Chronic Low Back Pain</p>

Abstract: PurposeAlthough chronic low back pain (CLBP) has profound effects on patients, society, and economy, its causes are difficult to identify. Psychogenic effects or social stress is known to affect CLBP; hence, investigation of its underlying causes requires a multifactorial approach. We determined the factors associated with CLBP by using an Internet-based survey. To prevent CLBP, we need to understand its cause and background.Patients and methodsA total of 1000 participants either with (+) or without (−) CLBP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 55 publications
0
31
0
Order By: Relevance
“…However, a sleep duration of more than 8 h per night did not result in a significant association with CLBP [57]. Ouchi et al (2019) found higher odds of a sleep duration of less than 6 h in CLBP patients compared to a sleep duration of 6 to 7 h per night [51]. No association was present in this study for a sleep duration of more than 7 h per night and CLBP compared to 6 to 7 h [51].…”
Section: Association Between Sleep Duration and Clbpmentioning
confidence: 60%
See 3 more Smart Citations
“…However, a sleep duration of more than 8 h per night did not result in a significant association with CLBP [57]. Ouchi et al (2019) found higher odds of a sleep duration of less than 6 h in CLBP patients compared to a sleep duration of 6 to 7 h per night [51]. No association was present in this study for a sleep duration of more than 7 h per night and CLBP compared to 6 to 7 h [51].…”
Section: Association Between Sleep Duration and Clbpmentioning
confidence: 60%
“…To comply with this research question, eligible studies on the interaction between sleep and chronic spinal pain variables were found. The data extraction of the 27 included studies resulted in a majority reporting the presence of an association between sleep and chronic spinal pain parameters [11][12][13][34][35][36][37][38][39][40][41]43,[45][46][47][49][50][51][52][53][54][55][56][58][59][60]. Thus, sleep quality, insomnia and sleep deprivation severity (i.e., sleep quantity), sleep disturbance, and sleepiness were found to be correlated with pain intensity in such a way that higher pain intensity levels were found in CSP patients reporting poorer sleep.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, 37 articles reporting on 36 unique studies were deemed eligible and selected. 34-70 Some articles appeared to be relevant upon initial review, but were excluded because the independent effects of the nine healthy buildings determinants could not be concluded. 71-78
Figure 1.PRISMA flow diagram of search results.
…”
Section: Resultsmentioning
confidence: 99%